Overview of GaAs und CdTe Pixel Detectors Using Medipix Electronics. Issue 9 (13th August 2020) - Fiederle, Michael; Procz, Simon; Hamann, Elias; Fauler, Alex; Fröjdh, Christer
Abstract: GaAs and CdTe pixel detectors have been developed over the last few decades. The applications of these detectors include X‐ and gamma‐ray detectors working at room temperature. Fundamental properties such as detection efficiency and noise are determined by the material properties of the sensor material. Different materials have been evaluated over the years in search of the best choice for different types of radiation. This article describes the properties of GaAs and CdTe materials for single photon processing pixel detectors using the Medipix electronics. Abstract : A recent development in GaAs and CdTe pixel detectors is described for the application of X‐ and gamma rays. Herein, the properties of GaAs and CdTe materials for single photon processing pixel detectors using the Medipix electronics are summarized.